Bio-hybrid carbon fibre/OPFF epoxy composites: mechanical, interfacial, and thermal performance - Randis Randis; Hadi Hermansyah; Syahruddin Syahruddin; Karmila Achmad; Yasmin Zulfati Yusrina; Devina Sanchia Samosir; Edi Wibowo; Rudianto Raharjo (Politeknik Negeri Lhokseumawe, 2026)
The development of sustainable lightweight composites with reliable structural integrity is important for transportation and construction applications. This study investigates a bio-hybrid sandwich composite comprising carbon fibre skins and Oil Palm Frond Fibre (OPFF) as a natural porous core, with emphasis on improving interfacial integrity through chemical modification. The primary objective is to evaluate the effectiveness of sequential NaOH and H₂O₂ treatment in enhancing mechanical performance, interfacial bonding, and thermal stability of the composite system. Hybrid composites were fabricated using an epoxy matrix, combining carbon fibre reinforcements with untreated and chemically treated OPFF cores in various fibre configurations. Mechanical properties were assessed under tensile, flexural, and impact loading, while interfacial morphology and thermal behaviour were examined using microscopy and thermal analysis. The results demonstrate that NaOH + H₂O₂ treatment improves composite performance, with treated unidirectional hybrids exhibiting the highest tensile and flexural strengths. Microscopic observations reveal a substantial reduction in fibre pull-out, debonding, and skin–core delamination, indicating enhanced interfacial integrity and more efficient load transfer. In addition, treated composites show improved thermal stability. The novelty of this work lies in demonstrating that chemically treated OPFF can function as a sustainable sandwich core, where improved interfacial bonding plays a decisive role in suppressing delamination and enhancing overall composite performance.